2022
DOI: 10.3390/nu14081618
|View full text |Cite
|
Sign up to set email alerts
|

Does Adherence to the Mediterranean Diet Have a Protective Effect against Asthma and Allergies in Children? A Systematic Review

Abstract: Dietary pattern may potentially impact on the pathogenesis of asthma and allergies. The Mediterranean Diet (MD) has significant health benefits due to its antioxidant and anti-inflammatory properties. The aim of this systematic review was to investigate the effectiveness of adherence to the MD against asthma and allergies in childhood. Hence, a systematic literature search was conducted on PubMed, ESBCO (Cinahl), Scopus, and the Cochrane Library databases up to 26 January 2022. The total number of articles obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…A recent systematic review assessed the association between a Mediterranean diet and asthma in childhood from the current literature and found an overweight of studies suggesting this association but concluded that RCTs are warranted due to limitations and heterogeneity of the studies. 71 In addition to the Mediterranean diet as a pattern, vitamin C related fruit intake such as citrus and kiwi fruits among a large TA B L E 1 An overview of current evidence of dietary prevention of childhood asthma. Italian cohort of school children age 6-7 years was associated with a significantly reduced prevalence of wheeze, nocturnal cough and chronic cough.…”
Section: Macronutrients and Dietary Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review assessed the association between a Mediterranean diet and asthma in childhood from the current literature and found an overweight of studies suggesting this association but concluded that RCTs are warranted due to limitations and heterogeneity of the studies. 71 In addition to the Mediterranean diet as a pattern, vitamin C related fruit intake such as citrus and kiwi fruits among a large TA B L E 1 An overview of current evidence of dietary prevention of childhood asthma. Italian cohort of school children age 6-7 years was associated with a significantly reduced prevalence of wheeze, nocturnal cough and chronic cough.…”
Section: Macronutrients and Dietary Patternsmentioning
confidence: 99%
“…Therefore, due to the biological plausible effects of a Mediterranean diet on childhood asthma it may be considered as a secondary prevention tool that needs to be further investigated in future studies. A recent systematic review assessed the association between a Mediterranean diet and asthma in childhood from the current literature and found an overweight of studies suggesting this association but concluded that RCTs are warranted due to limitations and heterogeneity of the studies 71 …”
Section: Dietary Secondary Prevention Of Childhood Asthmamentioning
confidence: 99%
“…Foods and nutrients play an important role in the protection of the airways and lungs against oxidative damage. This is evident, for example, from the observation that reduced consumption of fruits and vegetables results in decreased levels of defense antioxidants, thereby increasing the susceptibility to inhaled irritants [ 93 , 94 , 95 ]. Furthermore, low intake of fruits, vegetables, juices, and vitamins (A, C, and E) was linked to deficits in lung function in children [ 96 ], and an association between low serum vitamin A levels and airway obstruction has been shown in healthy adults [ 97 ].…”
Section: Oxidative Stress and Inflammation In Asthmamentioning
confidence: 99%
“…Another systematic review reported that increased adherence to the Mediterranean diet was negatively associated with asthma symptoms in children [106]. More recently, a systematic review indicated a protective role of the Mediterranean diet on childhood asthma [107]. On the other side, school-aged children, who follow a strict Western diet high in total and saturated fat and processed foods, seem to be at a higher risk of asthma [33].…”
Section: Dietary Patternsmentioning
confidence: 99%